(3aJhM GdESdGe dHdGO GdYLe hNQGSGfs - (3eMeO Hf YeQ Hf hGbO GdSgej GdCSdej HGdhdGA, GdeOfj, CHh YHO Gddg, GdhGbOj,J (B207 (3g` s ((3MSf YHOGdQRGb GdfGSN s)
(3ChdgG (B:s
(3GdaQS hLQi GdYjQHjf jOjg LQjkG TOjOkG s
(3BNQgG (B:s
(3hbOCYQVfG aj cJGHfG gPG Yf PcQ bJd YKeGf deG ajg ef GdCehQ GdJi dGJWjbgG GdCSeGY s
(3YdjgG JedcGJ HGSe eMeO BUa SfI (B1308(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B311 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B95s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B208 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B308 s
Keywords: (3GdJGQjNs